Annual Report together with financial statement for the year 1990 - River state government; river state government (Nigeria : River state, 1990)
This financial report emanated from the river state accountant general office. The paper provides insight into government capital and recurrent expenditure for the financial year 1990.
asm; 12/04/19
Loans
Keywords: Budget- estimates; Nigeria